2020
DOI: 10.1136/bmjopen-2019-034056
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying gender disparity in physician authorship among commentary articles in three high-impact medical journals: an observational study

Abstract: BackgroundScholarship plays a direct role in career advancement, promotion and authoritative recognition, and women physicians remain under-represented as authors of original research articles.ObjectiveWe sought to determine if women physician authors are similarly under-represented in commentary articles within high-impact journals.Design/Setting/ParticipantsIn this observational study, we abstracted and analysed author information (gender and degree) and authorship position from commentary articles published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…[11][12][13] There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia. 5,6,8,[19][20][21][22][23][24] This is independent of eld and has been documented even in elds which are predominantly comprised of women, such as pediatrics. 7 With regard to ophthalmology speci cally, our ndings are very similar to a recent study of multiple medical elds which found 36% of rst author (compared with our 37% of all, Cochrane and non-Cochrane, rst authors), and 24% of last author positions (compared with our 25% of all corresponding author positions which were most often last authors) to be held by women.…”
Section: Discussionmentioning
confidence: 96%
“…[11][12][13] There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia. 5,6,8,[19][20][21][22][23][24] This is independent of eld and has been documented even in elds which are predominantly comprised of women, such as pediatrics. 7 With regard to ophthalmology speci cally, our ndings are very similar to a recent study of multiple medical elds which found 36% of rst author (compared with our 37% of all, Cochrane and non-Cochrane, rst authors), and 24% of last author positions (compared with our 25% of all corresponding author positions which were most often last authors) to be held by women.…”
Section: Discussionmentioning
confidence: 96%
“…There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia [5,6,8,[19][20][21][22][23][24]. This is independent of field and has been documented even in fields which are predominantly comprised of women, such as pediatrics [7].…”
Section: Discussionmentioning
confidence: 99%
“…Workforce disparities for women in rheumatology almost certainly play some role in physician burnout. Many female physicians also report encountering sex or gender-based discrimination in the workplace, and fewer females are represented in leadership and mentor positions (40)(41)(42)(43). On the other hand, the higher clinical activity of male rheumatologists may indicate that men are more likely to be the primary income earner in their household (44), placing higher demands on them to see more patients.…”
Section: Discussionmentioning
confidence: 99%